Organizational talk: an investigation into how banking employees informally influence work culture towards their interests - Koch, Conrad (My University, 2010)
Abstract: The aim of this project has been to examine, anthropologically, the ways in which the employees in the head offices of two major South African banks engaged in informal communication, particularly gossip and humour, to affect their workplace culture towards their interests. The theoretical terrain was strongly influenced by the works of Erving Goffman (1959), Michel Foucault (1980), and post-structural feminist thought on identity politics and organisations. Using participant observation and semi-structured interviews it was found that 1) a major line of similarity between both organisations was a significant drive towards professionalism and performance in recent years, 2) a major line of difference being in how the cultural changes occurred, and in turn how micropolitical dynamics of gossip and humour were engaged in actual interactions, 3) these differences exemplified the local and strategic nature of race, age, gender, class, ethnicity, and other identity positions, as workers called on appropriate narratives in the light of personal interests. This work, I would hope, has demonstrated the theoretical strength of drawing on both Goffman and Foucault to explain face to face interaction, and most importantly has drawn to light the actual daily and localized nature of the struggles to change South African workplaces in the light of their history of privilege and discrimination.